Sport swimming and mental health: Is there a relationship? - Nunes, Leonardo Geamonond (2020)
Swimming is one of the most widely practiced individual sports globally, and its health benefits include a biopsychosocial axis. By interacting with the aquatic environment, the person experiences skills in an environment entirely different from where we live. However, few contributions have been recorded in the scientific literature regarding swimming and its benefits on mental health. There is a need for studies that address the benefits of this practice, training intensities, and ideal volumes, methods used, and weekly frequency that correspond to the psychophysiological responses triggered in children, adults, and seniors.